Hubungan antara Kualitas Tidur dengan Kadar Glukosa pada Pasien Diabetes Melitus Tipe 2 - Mariam Umar; Andi Surya Kurniawan (Media Husada Journal Of Nursing Science, 2026)
Low physical activity and poor sleep quality in Diabetic Mellitus (DM) patients exacerbate insulin resistance, leading to increased blood sugar levels through hormonal and metabolic disorders. Although type 2 DM cannot be cured, consistent management through blood sugar control and a healthy lifestyle can reduce the risk of complications and improve the quality of life of sufferers. The purpose of this study was to determine the relationship between sleep quality and glucose levels in patients with type 2 Diabetes Mellitus at Dr. Chasan Boesoirie Ternate Regional Hospital, North Maluku. The research design used was a cross-sectional approach with a population of 800 respondents and a research sample of 89 respondents taken using the consecutive sampling technique. Data were collected through interviews using the Pittsburgh Sleep Quality Index (PSQI) questionnaire and blood glucose level examination using GlucoDr. The variables studied were sleep quality as the independent variable and blood glucose levels as the dependent variable. The statistical test used was the Chi-Square test with a significance level of a = 0.05. The results of the study showed that the p value was 0.011 <0.05. So it can be concluded that there is a significant relationship between sleep quality and blood glucose levels in patients with type 2 diabetes mellitus at Dr. Chasan Boesoirie Regional Hospital, Ternate, North Maluku. Based on the results of this study, nurses should pay attention to fulfilling the rest and sleep needs of patients with diabetes mellitus.